Virtualization of culture as a defining trend development of modern society - Inna Hurova; Ольга Добродум (Cхід)
The article analyses various aspects of the modern society’s development related to the virtualisation of culture: the educational process, the cultural industries, the artistic sphere, the use of artificial intellect (AI) and artificial intellect and commemorative practices. The authors describe the origin of the term "virtuality" and its evolution in a scientific discourse. The emergence and evolution of the phenomenon of virtuality is connected to the development of information and communication technologies (ICT). The concept of "virtuality" is considered as an information and technical space, a technically mediated environment, an information resource of modern society and a media environment of culture. On the basis of the methodological approaches by the world’s researchers of the information society M. McLuhan and M. Castells, to the formation of a new type of culture, it is concluded that the intensification of the virtualisation process gradually leads to the replacement of the real subject space by the space of images, symbols and signs in many socially important spheres of human activity. It is shown that virtualisation contributes to the creation of innovative technologies of cultural and interpersonal communication and offers a new form of interaction with artefacts that have a virtual representation. The article highlights the increasing hybridisation of online and offline spaces, the transformation of the Internet into a space of human communication, everyday activities and entertainment. The authors note that modern innovations cannot replace the effect of a "live visit", but thanks to digital progress and widespread digitalisation, the development of 3D technologies, people have the opportunity to react emotionally to world events by being virtually in the centre of them. Virtualisation is seen as a new technology of representation that will largely determine the cultural experience of humanity in the nearest future. The authors show that the Internet now appears to users as an integrator of all spheres of social reproduction, and that various forms of cultural convergence and networking are being recorded in the Global Web. The benefits, threats and risks of the widespread use of modern information products are examined.